CLASSROOM CLIMATE AND ACHIEVEMENT MOTIVATION OF HIGHER SECONDARY SCHOOL STUDENTS IN KANYAKUMARI DISTRICT - M, Sutha; P, Shirlin (International Journal of Research -GRANTHAALAYAH, 2017)
The present study was conducted to know the Classroom climate and Achievement motivation of higher secondary school students in Kanyakumari District. The investigator collected data from 420 higher secondary school students by stratified random sampling method. Classroom Climate Inventory and Achievement Motivation Scales were used as tools. The data obtained were analysed by using appropriate statistical techniques like t-test, ANOVA and correlation. The obtained results showed that there exists a significant substantial correlation between Classroom climate and Achievement motivation of higher secondary school students. Achievement motivation based on the medium of instruction of higher secondary school students found to be significantly higher than English medium students.